Tungsten impurity reduction by ICRH in a high power injection and high performance H-mode discharge on EAST - Zhen Zhou; Shengyu Shi; Ling Zhang; Tao Zhang; Xiaohe Wu; Yunxin Cheng; Wenmin Zhang; Chaowei Mai; Shengyu Fu; Yifei Jin; Xiang Jian; Kaixuan Ye; et al. (Nuclear Fusion)
The decrease in tungsten (W) content with the higher ion cyclotron resonance heating (ICRH) power is observed and explained for the first time in a high power injection ( P _inj > 10 MW), high performance ( β _N ∼ 2, β _P ∼ 2.8, n _e / n _GW ∼ 80%, f _BS ∼ 60%) H-mode discharge on experimental advanced superconducting tokamak. Unlike the previous phenomenon of electron cyclotron resonance heating core W control (Shi et al 2022 Nucl. Fusion 62 066031), there is a slight change in the background plasma temperature when higher ICRH is applied, but the toroidal rotational velocity decreases by ∼10 km s ^−1 . Under this condition, the intensity of W unresolved transition array spectral structure in the region of 45–70 Ǻ (which is composed of W ^27+ -W ^45+ line emissions) and W ^44+ density through spectroscopy in the Extreme Ultraviolet region decreases markedly. In addition, the poloidal asymmetry of radiation distribution from the tomographic inversions of Soft x-ray emission is reduced obviously. Theoretical modeling results indicate that the reduction in toroidal rotation leads to less W poloidal asymmetry and neoclassical pinch, which is more efficient in alleviating the core W accumulation than the improvement of isotropic hydrogen (H) minority temperature. The effects of isotropic and anisotropic H minority from ICRH on W transport are compared in the simulation lastly.